The devil and the Victorians - Bartels, Sarah, 1991- author.
1 online resource.
Keywords: "In recent decades, there has been a growing recognition of the significance of the supernatural in a Victorian context. Studies of nineteenth-century spiritualism, occultism, magic, and folklore have highlighted that Victorian England was ridden with spectres and learned magicians. Despite this growing body of scholarship, little historiographical work has addressed the Devil. This book demonstrates the significance of the Devil in a Victorian context, emphasising his pervasiveness and diversity. Drawing on a rich array of primary material, including theological and folkloric works, fiction, newspapers and periodicals, and broadsides and other ephemera, it uses the diabolic to explore the Victorians' complex and ambivalent relationship with the supernatural. Both the Devil and hell were theologically contested during the nineteenth century, with an increasing number of both clergymen and laypeople being discomfited by the thought of eternal hellfire. Nevertheless, the Devil continued to play a role in the majority of English denominations, as well as in folklore, spiritualism, occultism, popular culture, literature, and theatre. The Devil and the Victorians will appeal to readers interested in nineteenth-century English cultural and religious history, as well as the darker side of the supernatural"--